1997
DOI: 10.1080/02701367.1997.10608002
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation Enhances Intermittent Work Performance

Abstract: To determine the impact of creatine supplementation on high-intensity, intermittent work, 18 participants each performed 2 sets of 4 different work bouts to exhaustion. For 5 days prior to the first set of work bouts, all participants received a placebo (5 g of calcium chloride daily). For the second set of work bouts, 9 participants again received the placebo, while the other 9 received creatine supplementation (18.75 g creatine monohydrate daily for 5 days prior to and 2.25 g creatine daily during testing). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 7 publications
3
34
0
3
Order By: Relevance
“…Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect. Moreover, lactate concentrations were not influenced by creatine supplementation in the present study, which supports the hypothesis that the glycolytic pathways were unaltered by creatine supplementation as proposed by Birch et al 2 Many studies in the past reported positive effects on performance of different types and durations after a short-term creatine supplementation, [1][2][3][4][5][6][7][8]21 whereas others found no effect. 16,[22][23][24][25][26] Interestingly, in most of the studies showing no ergogenic effect on exercise performance after creatine supplementation, a time or distance trial was performed, [22][23][24][25][26] whereas in studies with a positive effect the time to exhaustion at a given workload was determined.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect. Moreover, lactate concentrations were not influenced by creatine supplementation in the present study, which supports the hypothesis that the glycolytic pathways were unaltered by creatine supplementation as proposed by Birch et al 2 Many studies in the past reported positive effects on performance of different types and durations after a short-term creatine supplementation, [1][2][3][4][5][6][7][8]21 whereas others found no effect. 16,[22][23][24][25][26] Interestingly, in most of the studies showing no ergogenic effect on exercise performance after creatine supplementation, a time or distance trial was performed, [22][23][24][25][26] whereas in studies with a positive effect the time to exhaustion at a given workload was determined.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies investigated the influence of creatine supplementation on leg muscle performance. [1][2][3][4][5][6]8,9,16,[24][25][26] Since arm muscles contain more type II fibres than leg muscles and since type II fibres have initially a higher phosphocreatine content than type I fibres, 15 it could be hypothesised that creatine supplementation would be less efficient for arm exercise, an assumption that is supported by our findings. However, this hypotesis has to be investigated in further studies, as one cannot conclude definitely if an initially higher phosphocreatine content of arm muscles limits the effectiveness of a creatine supplementation in this muscle group.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Throughout the 6-week study, both groups were subjected to the same training protocol of the 'Power (1), Rep-Range (2), Shock (3)' mode [18], every element dominating in weekly microcycles. The microcycles differed in the kinds of exercise (eccentric, concentric, mixed), intensities and intermission durations, as well as in the so-called stick point isometric elements [9,22].…”
Section: Methodsmentioning
confidence: 99%